MODELING OF INVESTMENT OF HEALTH CARE ON REGIONAL LEVEL - Martseniuk, V. P.; Vakulenko, D. V.; Skochilyas, S. M. (Medical Informatics and Engineering, 2020)
Background. An investment model of health care is proposed, which focuses on maintaining high investment activity and a relative improvement in the competitiveness of the region. Today in Ukraine the level of investment activity and reproduction of the market segment of innovative products remains insufficient to ensure an innovative breakthrough of the national economy. Under such conditions, the core of the modern Ukrainian model of economic competitiveness should be the implementation of an innovative model of structural adjustment of the economy, and in the future — the implementation of the strategy of the knowledge economy. The aim was systematization of conceptual approaches to the evaluation and modeling of regional investment activities in the field of health care and the selection of the most valuable elements, the generalization of which will form a proper theoretical and methodological basis. Materials and methods. Results. Based on a model for managing the development of the medical industry using a system of nonlinear ordinary differential equations with two distributed lateness, an economic interpretation of each is presented. This condition can be considered as one of the conditions for the investment attractiveness of the healthcare industry. Construction of a mathematical model of reorganization of the investment potential of the health care sector of the region, its qualitative analysis, study of stationary solutions of its stability and conducting a numerical experiment. Conclusions. Today, it is necessary to carry out certain managerial and organizational measures aimed at reforming the health care system of Ukraine. They should concern updating of mechanisms of state management of branch, scientific substantiation and practical introduction of new methods of management that would promote improvement of infrastructural potential of health care, modernization of medical institutions, creation of new means of production on the basis of modern techniques and advanced technologies, intensifying the development of investment strategy for socioeconomic development. The perspective of this study is to study the model of management of the development of the medical industry in the region on the control of managerial, investment and legislative factors.